The Concept of Psychological Well-Being for the Elderly: The Perspective of Abu Hamid Muhammad Al-Ghazali - Rahmah, Mamluatur; Muhaya, Abdul; Bukhori , Baidi; Imas Masrifatul Khoeriyah (Mimbar Agama Budaya, 2025)
This article explores the concept of psychological well-being for the elderly according to Abu Hamid Muhammad al-Ghazali, highlighting the psychological problems of contemporary seniors. In old age, individuals often face loneliness, reduced social roles, loss of meaning in life, and anxiety about death. These conditions indicate that well-being cannot be adequately explained through physical or social aspects alone, but also requires an understanding that touches on the spiritual dimension. In modern psychology, well-being is usually understood through self-acceptance, positive relationships, autonomy, life purpose, and personal growth. However, although spirituality is taken into account, it has not yet gained a complete position in the theoretical framework. Al-Ghazali offers a Sufi framework that emphasizes that true well-being (sa'ādah) is rooted in four pillars: ma'rifat al-Nafs, ma'rifat allah, ma'rifat al-'Ālam, and ma'rifat al-Ākhirat. Using a qualitative method based on philosophical-textual studies, this research found that the psychological well-being of the elderly is an integrative process that encompasses psychological, moral, and spiritual dimensions with a transcendental orientation as the main foundation.